Penguatan Literasi Keuangan Syariah Pada Penyandang Disabilitas - Ahmad Ma’ruf; Joko Prihatin; Novia Rahmayanti (Universitas Muhammadiyah Yogyakarta, 2019)
Financial literacy is a basic need for everyone, including people with disabilities to avoid financialproblems. The financial sector has been effective in encouraging the development of thehousehold economy, both in terms of capability and accuracy of spending, business financing, and theaccuracy of savings and investment choices. Adults with disabilities who are members of the GADINGcommunity have a majority of secondary education with limited financial management, and are notaccustomed to household financial planning. Dissemination activities are carried out through structuredtraining that begins with a process of social analysis, needs analysis, and training design that is adaptedto disability conditions. The results of this activity are still minimal, so it needs to be repeated periodically.